Does food insecurity compromise maternal dietary Zinc or energy intake in favor of her child, in rural poor Mexican households? ¿En hogares rurales pobres de México, la inseguridad alimentaria compromete el consumo de zinc y energía de las madres en favor de sus hijos? - Karla Moreno-Tamayo; Teresita González de Cossío; Mario Flores-Aldana; Sonia Rodríguez-Ramírez; Luis Ortiz-Hernández (Salud Pública de México, 2011)
OBJECTIVE: To analyze quantitative indicators of food insecurity (FI), and estimate if FI modifies the association between maternal and child Zinc and energy intake as evidence for maternal dietary compromise in favor of her child. MATERIAL AND METHODS: Cross-sectional study (n=2 563), data derived from baseline impact evaluation of the Mexican Programa de Apoyo Alimentario. Quantitative indicators of FI were:Household food storage, maize and/or bean production, food expenditure, and spatial access to food markets. We evaluated percentage adequacy of energy (PAE) and Zinc (PAZn) intake. Multiple linear regression model was fitted to estimate the association between maternal and child PAE and PAZn. RESULTS: Child PAE and PAZn were positively associated with those of their mothers. None of the FI indicators modified the association between maternal and child PAE and PAZn. CONCLUSIONS: No evidence of maternal dietary compromise in favor of her child was observed using four quantitative indicators of FI in central-southern rural Mexican househods. OBJETIVO: Analizar indicadores cuantitativos de inseguridad alimentaria (IA) y estimar si IA modifica la asociación del consumo de energía y zinc en madres e hijos como evidencia del compromiso de la dieta materna a favor de su hijo. MATERIAL Y MÉTODOS: Estudio transversal,información basal de la evaluación de impacto del Programa de Apoyo Alimentario. Indicadores de IA: reserva de alimentos en hogar, autoproducción maíz y/o frijol, porcentaje del gasto en alimentos y acceso físico a mercados de alimentos.Se calculó el porcentaje de adecuación del consumo energético (PAE) y Zinc (PAZn) (n=2 563 pares). Se estimó un modelo de regresión lineal ajustado por covariables. RESULTADOS: El PAE y PAZn de madres e hijos se asoció positivamente. Ningún indicador de IA modificó la asociación entre PAE y PAZn materno con respecto a sus hijos. CONCLUSIONES: Los indicadores de IA estudiados no modifican la relación entre la dieta de madres-hijos en hogares rurales de México.